2016
DOI: 10.1007/s11745-016-4214-1
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids from a Glass Sponge Aulosaccus sp. Occurrence of New Cyclopropane‐Containing and Methyl‐Branched Acids

Abstract: In order to identify new structures, the free fatty acids from an extract of a glass sponge Aulosaccus sp. (from the north-west Pacific) belonging to one of the least chemically investigated classes (Hexactinellida), were fractionated by RP-HPLC and analyzed by NMR spectroscopy and GC-MS of their pyrrolidine derivatives, methyl(ethyl) esters and their dimethyl disulfide adducts. One hundred and twenty-three C-C acids (including nine new compounds) were detected, one hundred and ten of these compounds have not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Chemicals: Methyl oleate (9-cis-octadecenoate; Fluka Chemie AG), elaidate (9-trans-octadecenoate; Sigma-Aldrich), palmitoleate (9cis-hexadecenoate), palmitelaidate (9-trans-hexadecenoate; Gasukuro Kogyo Inc. Japan), 15-cis-(2R)-2-hydroxydocosenoate, 16-cis-(2R)-2-acetyloxytricosenoate [11], oleic (9-cis-octadecenoic acid; Sigma), nervonic (15-cis-tetracosenoic; Sigma-Aldrich), 5cis,9-cis,22-cis-nonacosatrienoic [12] acids were used. The methyl 15-cis-(2R)-2-hydroxydocosenoate (0.7 mg), methyl 16-cis-(2R)-2acetyloxytricosenoate (1.2 mg) and 15-cis-tetracosenoic acid (6.0 mg in two drops of CHCl 3 ) were converted into corresponding trans-isomers using a modified procedure [13] of isomerization with nitrogen oxides (1.5 h at 25−30 ºC: NaNO 2 , 5 mg, and water, 20 mkl, and 50 % aqueous solution of HNO 3 , 50 mkl, in a capped vial).…”
Section: Methodsmentioning
confidence: 99%
“…Chemicals: Methyl oleate (9-cis-octadecenoate; Fluka Chemie AG), elaidate (9-trans-octadecenoate; Sigma-Aldrich), palmitoleate (9cis-hexadecenoate), palmitelaidate (9-trans-hexadecenoate; Gasukuro Kogyo Inc. Japan), 15-cis-(2R)-2-hydroxydocosenoate, 16-cis-(2R)-2-acetyloxytricosenoate [11], oleic (9-cis-octadecenoic acid; Sigma), nervonic (15-cis-tetracosenoic; Sigma-Aldrich), 5cis,9-cis,22-cis-nonacosatrienoic [12] acids were used. The methyl 15-cis-(2R)-2-hydroxydocosenoate (0.7 mg), methyl 16-cis-(2R)-2acetyloxytricosenoate (1.2 mg) and 15-cis-tetracosenoic acid (6.0 mg in two drops of CHCl 3 ) were converted into corresponding trans-isomers using a modified procedure [13] of isomerization with nitrogen oxides (1.5 h at 25−30 ºC: NaNO 2 , 5 mg, and water, 20 mkl, and 50 % aqueous solution of HNO 3 , 50 mkl, in a capped vial).…”
Section: Methodsmentioning
confidence: 99%
“…The 1 Н-NМR spectrum of these compounds also showed signals of the terminal methyl groups of dominant normal-chain (δ Н 0.88, t, J = 6.9 Hz) and minor cyclopropane-containing (δ Н 0.89, t, J = 6.9 Hz) constituents. Under our conditions of hydrogenation, ring opening was not the dominant process for the minor constituent, so the signals of cis-cyclopropane protons at δ Н −0.33 (dt, J = 4.2, 5.5 Hz), 0.56 (ddd, J = 4.2, 8.3, 8.3 Hz), and 0.645 (m) [32] were observed. The hydrolysis of derivatized oxidized cerebrosides from part 2 with subsequent acetylation of products gave three sphingoid base derivatives.…”
Section: Analyses Of Fas Sphingoid Bases and Sugar Obtained From Oxidized Cerebrosidesmentioning
confidence: 76%
“…In particular, some bacterial branched-chain, cyclopropane-containing FAs, and their monoenoic precursors were present in significant amounts in Aulosaccus sp. [32], and an overwhelming number of the sterols (stanols, ∆ 5 -, ∆ 7 -, and ∆ 8 (14) -sterols) of this sponge were oxidized to the corresponding 3-ketosteroids [37]. The occurrence of these FAs and steroids in Aulosaccus sp.…”
Section: Oxidized Cerebrosides From the Extract Of Aulosaccus Sp: Structures And Possible Originsmentioning
confidence: 88%
“…Our earlier study 46 indicated that Aulosaccus sp. contained significant amounts of fatty acids of microbial origin.…”
mentioning
confidence: 95%
“…suggested that this sponge was associated with mycobacteria or related microbes. 46 Notably, the bacteria of this group (phylum Actinobacteria) are not only known as sponge specific microorganisms, 47 but these microbes are also potent steroid degraders, particularly active in the catabolism of sterols. 48 The proposed oxidation of sterols in Aulosaccus sp.…”
mentioning
confidence: 99%